Influence Live Shopping And Affiliate Marketing On Impluse Buying On Tiktok Shop Application - Muhammad Burhanudin; Misbak Misbak; Jefri Romdony (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the effect of Live Shopping and Affiliate Marketing on Impulse Buying behavior among active Tiktok users. Using a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM), data were collected from 150 respondents dominated by young consumers aged 17–24 years, consisting mainly of students and university learners. The results of the direct effect hypothesis testing show that: (1) Live Shopping has a positive and significant effect on Impulse Buying with an original sample value of 0.376, supported by a t-statistic of 4,696 (>1.96) and a p-value of 0.000 (<0.05), indicating that H1 is accepted; (2) Affiliate Marketing has a strong positive and significant effect on Impulse Buying with an original sample value of 0.718, supported by a t-statistic of 8.911 (>1.96) and a p-value of 0.000 (<0.05), confirming that H2 is accepted; and (3) Live Shopping and Affiliate Marketing simultaneously have a significant effect on Impulse Buying, supported by a combined t-statistic of 7.319 (>1.96) and a p-value of 0.000 (<0.05), indicating that H3 is accepted. The findings confirm that interactive live promotional features and creator-based recommendation strategies effectively stimulate impulsive purchase decisions among young digital consumers. This study provides theoretical and practical contributions by emphasizing the importance of real-time engagement and social-persuasive marketing synergy in shaping impulse buying responses on e-commerce platforms